Checklist and Simple Identification Key for Frogs and Toads from District IV of The MADA Scheme, Kedah, Malaysia - Ibrahim Jaafar; Teoh Chia Chai; Shahrul Anuar Mohd Sah; Mohd Abdul Muin Md. Akil (Tropical Life Sciences Research, 2009)
A survey was conducted to catalogue the diversity of anurans in District IV of the Muda Agriculture Development Authority Scheme (MADA) in Kedah Darul Aman, Malaysia, from July 1996 to January 1997. Eight species of anurans from three families were present in the study area. Of these, the Common Grass Frog (Fejevarya limnocharis) was the most abundant, followed by Mangrove Frog (Fejevarya cancrivora), Long-legged Frog (Hylarana macrodactyla), and Common Toad (Duttaphrynus melanostictus). Puddle Frog (Occidozyga lima), Taiwanese Giant Frog (Hoplobatrachus rugulosus), and Banded Bullfrog (Kaluola pulchra) were rare during the sampling period, and only one Paddy Frog (Hylarana erythraea) was captured. A simple identification key for the anurans of this area is included for use by scientists and laymen alike. Satu kajian telah dilakukan untuk mendapatkan senarai spesies katak dan kodok daripada Kawasan IV Projek Lembaga Kemajuan Pertanian Muda (MADA), Kedah Darul Aman, Malaysia bermula dari Julai 1996 hingga Januari 1997. Hasil menunjukkan bahawa terdapat lapan spesies anura daripada tiga famili berada di kawasan kajian tersebut. Katak Rumput (Fejevarya limnocharis), adalah spesies dengan kelimpahan tertinggi diikuti oleh Katak Bakau (Fejevarya cancrivora), Katak Kaki Panjang (Hylarana macrodactyla) dan Katak Puru (Duttaphrynus melanostictus). Tiga spesies lain iaitu Katak Limbah (Occidozyga lima), Katak Taiwan (Hoplobatrachus rugulosus) dan Katak Betong (Kaloula pulcra), jarang ditemui sementara hanya seekor Katak Padi (Hylarana erythraea) yang ditangkap. Pemeriksaan ke atas spesimen-spesimen ini telah menghasilkan satu kekunci pengenalan untuk katak-katak di sini yang boleh digunakan oleh para saintis dan juga orang biasa.